A legal study of sexual harassment in private higher education institution in Malaysia: policy consideration / Sairun Syakira Saiman - Saiman, Sairun Syakira (2018)
This study was conducted to investigate the policy consideration of Sexual Harassment in Private Higher Education Institution in Malaysia. The study involved the comparative on regulation available in Malaysia and other countries in govern the sexual harassment offence especially towards the tertiary education level. The prevalent studies also said that, the sexual harassment is one of contemporary silent issues in academic setting. The experience of sexual harassment in schools and institutions of higher learning is a serious social problem which could worsen the woeful academic performance of the victims. In this research, there are two different approaches being used: (i) qualitative (comparing the available regulative measure) and (ii) quantitative approaches (conduct interview among the staff and distribute the survey form to the students in selected private higher education within Kuala Lumpur and Klang Valley area). The results showed that there are a number of students who experienced sexual harassment during the study in the private college respectively. Supported with the statistic of the sexual harassment reported in previous studies, it shows that, it is a need for the private higher education institution to implement the sexual harassment policy in their institution. For the interview conducted, two out of three interviewees strongly supported the implementation of sexual harassment policy in the private higher education institutions whilst one of the interviewee will support the implementation of the policy on sexual harassment in private higher education institution, providing that, the culture among the students could accept such policy. Another is, the way to implement the policy effectively. Besides, the other method used in this paper is, comparing the existing regulative measure on sexual harassment policy in higher education between Malaysia and other countries has been done. The result from the comparison of law made can be concluded that, policy or regulation has their own pre-eminence in uphold the rules on sexual harassment among the students. However, the researcher found that, there is no specific explanation in term of punishment (such as punishment of fine, whipped etc) being stated in the policy or law respectively especially in Malaysia. Therefore, the policy on sexual harassment in private higher education institution should be consider to be developed to provide a safety study environment and give the correct procedure whenever they faced the sexual harassment in study place respectively.